Escola e ócio estudioso: o papel formativo da gestora - Rizzi, Luciana Maria Schmidt (2024)
In this thesis, we present an investigation into the role of the manager, taking as a starting point the author's personal experience in promoting the school as a formative experiment and studious leisure, an indispensable condition for cultivating oneself with a view to the ethical transformation of subjects. In a context where everything becomes "productive time", the research problem consists of thinking about the role of the school manager in promoting education as training and self-education, based on studious leisure and "free time". The thesis asks about the formative role of the manager in the construction of the school as a space for scholarly leisure and proceeds to the interpretation of a set of bibliographies in order to establish a conceptual framework about the fundamental characteristics of this context, such as neoliberalism, training, Bildung, skholé , studious leisure and free time. We adopt a hermeneutic stance focused on reading and interpreting the delimited texts, which are essential for clarifying and approaching the themes listed in their relationship with training considered as self-formation of subjects. We argue that school management acts on one's own life and on the lives of others and, in this role, can constitute itself as a master of self-care through formative self-criticism of one's own experience. The reflections presented add up to a deepening of the author's own professional experience as an educator in the scope of school management, guided by the perspective of building the school as a place for studious leisure. Throughout the thesis, we recover the notion of school as free time, based on studious leisure, reconstructing some references from the classical tradition of Skholé and Ótium. We conclude that school management, in the role of director as governor of studious leisure, in the face of a school that is increasingly culturally deformed, occupies an important formative centrality. For this reason, the task of the educational manager, to be formative, needs to be guided by the scholarly leisure through which she governs, guides and guides the school.